2003
DOI: 10.3759/tropics.13.79
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of Sri Lankan Dipterocarpaceae in relation to other Asian Dipterocarpaceae based on chloroplast DNA sequences

Abstract: The Dipterocarpaceae, a well-known tropical tree family of Asian rainforests, is the most dominant component of Sri Lankan rainforests. The origin of Sri Lankan Dipterocarpaceae and their relationship with other Asian members of the family are still unknown. We studied this relationship using chloroplast DNA nucleotide sequences. DNA sequences of trnL-trnF spacer and trnL intron regions from 27 Sri Lankan species, and 62 other species belonging to 14 genera were included in the study. The neighbor joining (NJ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 25 publications
7
19
0
Order By: Relevance
“…Since then, several other phylogenetic studies on Dipterocarpaceae were reported based on chloroplast (cp) DNA sequences Gamage et al, 2003;Kajita et al, 1998;Kamiya et al, 1998;Morton et al, 1999) and the nuclear gene PgiC (Kamiya et al, 2005). However, previous studies on molecular phylogeny of the Dipterocarpaceae included either limited number of species Morton et al, 1999;Tsumura et al, 1996) or informative sites (Gamage et al, 2003;Kamiya et al, 1998) or both . The most recent work by Kamiya et al (2005) has mainly focused on the relationships of Shorea , Hopea, Neobalanocarpus and Parashorea genera and did not include species from the Dipterocarpeae tribe and species of the Doona genus (Kostermans, 1984;Kostermans, 1992;Maury, 1978;Maury-Lechon, 1979).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since then, several other phylogenetic studies on Dipterocarpaceae were reported based on chloroplast (cp) DNA sequences Gamage et al, 2003;Kajita et al, 1998;Kamiya et al, 1998;Morton et al, 1999) and the nuclear gene PgiC (Kamiya et al, 2005). However, previous studies on molecular phylogeny of the Dipterocarpaceae included either limited number of species Morton et al, 1999;Tsumura et al, 1996) or informative sites (Gamage et al, 2003;Kamiya et al, 1998) or both . The most recent work by Kamiya et al (2005) has mainly focused on the relationships of Shorea , Hopea, Neobalanocarpus and Parashorea genera and did not include species from the Dipterocarpeae tribe and species of the Doona genus (Kostermans, 1984;Kostermans, 1992;Maury, 1978;Maury-Lechon, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Frim, Kepong, Malayasia AB006419 AB006402 AB006385 Kajita et al (1998) Vatica bella V. Sl. Frim Arboretum, Malayasia AB246481 AB246546 AB246416 Present study, Gamage et al (2003) Vatica chinensis L. Gilimale, Sri Lanka AB246485 AB246550 AB246420 Present study, Gamage et al (2003) Vateria copallifera (Retzius) Alston Kanneliya Forest Reserve, Sri Lanka AB246496 AB246561 AB246431 Present study, Gamage et al (2003) Vateriopsis seychellarum Dyer Seychelles AB246497 AB246562 AB246432 Present study, Gamage et al (2003) Sub-family: Monotoideae…”
Section: Species Samplingmentioning
confidence: 99%
See 3 more Smart Citations